Exploration of Learning Implementation for Deaf Students During the Covid-19 Pandemic - Mabruroh, Alfina Fadilatul; Gunarhadi, Gunarhadi; Widyastono, Herry (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The Covid-19 pandemic has resulted in transformations in various fields of human life, one of which is education. The Covid-19 pandemic has forced the learning process to be carried out from home. All students, including deaf students, must study from home, and parents are required to be able to guide their children during the learning process at home. This study aims to explore the implementation of learning for deaf students during the Covid-19 pandemic. This research uses case study research method. Subjects involved in this study included teachers, deaf students, and parents. Data was collected using in-depth interviews and documentation studies. The analysis process was carried out in a qualitative descriptive manner. The results showed that during the Covid-19 pandemic, teachers made special teaching materials and conducted weekly assessments manually to facilitate deaf students. Deaf students or parents often go to school to pick up new teaching materials and bring last week's assessment results. This situation makes teachers need to make teaching for the deaf more simple and interesting to improve independent learning for students. The implication of this research is that the government provides special educational media for deaf children.